Relevance of treated cocaine users' retrospective memory of first cocaine use. (June 2018) - Karsinti, Emily; Piani, Kristel; Zerdazi, El Hedi; Maskos, Uwe; Faure, Philippe; Romo, Lucia; Bellivier, Frank; Brousse, Georges; Lépine, Jean Pierre; Bloch, Vanessa; Vorspan, Florence
Highlights: This study retrospectively assesses the subjective effects of first cocaine use. Those effects are variables among subjects. Four dimensions (Anxiety, Disinhibition, Tachypsychia and Calmness) are found. Dimensions are associated with a history of substance use, including cocaine. Tachypsychia during first cocaine use is associated with further dependence. Abstract: Little is known regarding between-subject variability in the subjective effects of first cocaine use. This study retrospectively assesses the subjective effects of first cocaine use in 160 current treatment-seeking cocaine use disorder patients. Subjective effects of first cocaine use were evaluated with an ad-hoc questionnaire used for cannabis effects. A principal component analysis (PCA) was performed, with resulting factors correlated with clinical variables (α = 0.05). Four factors emerged in the PCA, namely Anxiety (accounting for 21.5% of questionnaire variance), Disinhibition (17.3%), Tachypsychia (16%) and Calmness (13%). Male gender was associated with Disinhibition and Tachypsychia. Cocaine severity factors were associated with Disinhibition, Tachypsychia and Calmness. Opiate, sedative and poppers uses were associated with Anxiety, Tachypsychia and Calmness. The retrospective assessment of the subjective effects of first cocaine use shows significant variability. The different dimensions of subjective first effects are influenced by age, gender and previous substance use history, as well as characteristics of first cocaine use and cocaine-related outcomes.